The effects of alpha lipoic acid (ALA) supplementation on blood pressure in adults: a GRADE-assessed systematic review and dose-response meta-analysis of randomized controlled trials - Vajdi, Mahdi; Noshadi, Nooshin; Hassanizadeh, Shirin; Bonyadian, Atefeh; Seyedhosseini-Ghaheh, Hooria; Askari, Gholamreza (Frontiers in Cardiovascular Medicine, 2023)
There have been various clinical studies on the effect of Alpha lipoic acid (ALA) supplementation on blood pressure (BP), but the findings from these are contradictory.Therefore, we performed a systematic review and dose-response meta-analysis to summarize the relation of ALA supplementation and systolic blood pressure (SBP) and diastolic blood pressure (DBP) in adults. A comprehensive search was conducted in Medline (PubMed), Embase, Scopus, and ProQuest up to July 2023. Randomized controlled trials (RCTs) evaluating the effect of ALA on SBP and DBP were included. The pooled weighted mean difference (WMD) of included trials was estimated using a random-effects model. The dosedependent effect was also assessed. A total of 11 RCTs with the participation of 674 patients were included. The result of the meta-analysis indicated that using ALA supplementation significantly reduced the SBP (WMD= -5.46 mmHg; 95% CI: -9.27, -1.65; p <0.001) and DBP (WMD= -3.36 mmHg, 95% CI: -4.99, -1.74; p <0.001). The ALA administrations significantly reduced SBP and DBP at the dosages of < 800 mg/day, when administered for ≤ 12 weeks. The present meta-analysis revealed that ALA supplementation could exert favorable effects on SBP and DBP. Further well-designed studies with larger samples are needed to ascertain the long-term effects of ALA on BP.